The effect of programming on primary school students' mathematical and scientific understanding: educational use of mBot - Sáez-López, José-Manuel; Sevillano-García, Maria-Luisa; Vazquez-Cano, Esteban (Educational technology research and development, 2019)
This study highlights the importance of an educational design that includes robotics and programming through a visual programming language as a means to enable students to improve substantially their understanding of the elements of logic and mathematics. Gaining an understanding of computational concepts as well as a high degree of student participation and commitment emphasize the effectiveness of introducing robotics and visual programming based on active methodologies in primary education. Implementation of this design provides sixth-grade elementary education students with activities that integrate programming and robotics in sciences and mathematics; these practices allow students to understand coding, motion, engines, sequences and conditionals. A quasi-experimental design, descriptive analysis and participant observation were applied across various dimensions to 93 sixth-grade students in four primary education schools. Programming and robotics were integrated in one didactic unit of mathematics and another in sciences. Statistically significant improvements were achieved in the understanding of mathematical concepts and in the acquisition of computational concepts, based on an active pedagogical practice that instills motivation, enthusiasm, commitment, fun and interest in the content studied.